(untitled) (World Bulletin of Social Sciences, 2023)
The current study tests the correlation and effect relationship between organizational support (organizational justice, participation in decision-making, leader behavior that supports subordinates) and open innovation (the appropriate environment for innovation, the impact of innovation, the implementation of innovation) from. It is a main hypothesis, and the emergence of three sub-hypotheses, then A sample of faculty members in the College of Science, University of Al-Qadisiyah, which has a vital and prominent importance in the field of education and knowledge and its various practices in creating an educated, civilized and educated generation. Data was collected through a questionnaire prepared for this purpose. 60 questionnaires were distributed to faculty members, and 60 were retrieved. A questionnaire, and the recovery rate was 100%, and the SPSS vr 24 program was used. The results of the association and impact and the testing of hypotheses, where the validity of the hypotheses was found in the light of the results of the statistical analysis, and a number of recommendations were reached, perhaps the conclusion was that there is a positive correlation between support Organizational and open innovation, the more the study community encourages faculty members to participate in decision-making, this helps to increase open innovation among the study sample.